(untitled) (Palíndromo, 2014)
Hannah Arendt classifies the human activity in three different categories: labor, work and action. This article intends to relate these categories with the concept of technology according to various authors, such as Cupani, Dias and Epstein, who indicate that the technologi- cal object is broader than the common sense assumptions. Being the technological object closely related to Arendt’s concepts of production, we emphasized the importance of technologies in the human condition, since, for the author, it depends mainly on man’s capacity to produce. According to this context, this paper tries to establish a relation between man and machine, and the subjective relations proposed by the artistic object of the art technology, thereby analyzing the context in which man relates to machine in his environment, building through these relations and influences that permeate the entire culture.